2021
DOI: 10.1002/ehf2.13283
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left ventricular structure and function associated with renal transplantation: a systematic review and meta‐analysis

Abstract: Aims This study aimed to examine if the cardiac changes associated with uraemic cardiomyopathy are reversed by renal transplantation. Methods and results MEDLINE, Embase, OpenGrey, and the Cochrane Library databases were searched from 1950 to March 2020. The primary outcome measure was left ventricular mass index. Secondary outcome measures included left ventricular dimensions and measures of diastolic and systolic function. Studies were included if they used any imaging modality both before and after successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
(370 reference statements)
0
12
0
Order By: Relevance
“…In the study, there were no perioperative deaths, and close to 70% of the patients achieved LVEF >50% at 12 mo posttransplant 188 ; however, a recent meta-analysis on the same topic showed no improvement in LVEF after kidney transplant. 189 In the end, it remains difficult to predict who may benefit from kidney transplant alone and who requires simultaneous heart-kidney transplant.…”
Section: Hfrefmentioning
confidence: 99%
“…In the study, there were no perioperative deaths, and close to 70% of the patients achieved LVEF >50% at 12 mo posttransplant 188 ; however, a recent meta-analysis on the same topic showed no improvement in LVEF after kidney transplant. 189 In the end, it remains difficult to predict who may benefit from kidney transplant alone and who requires simultaneous heart-kidney transplant.…”
Section: Hfrefmentioning
confidence: 99%
“… [16] , however, reported that the prevelance of LVH modestly decreased from 51.2% to 50% after 1 year of KT in which about 30% of patients with LVH prior to transplantation had LVH regression after transplantation while 30% of patients had a new onset of LVH after transplantation, similar with the current study in that the prevalence of LVH non-significantly changed from 39% to 39.6% after the 2 year follow-up in which patients with a new onset LVH and LVH regression were equal at about 10.8%. The current meta -analysis also demontrated no improvement of left ventricular structure and function after KT [18] . In addition to graft function, hypertension and anemia associated with post-KT LVH, mode of dialysis treatment before transplantation, a history of acute allograft rejection, and patent VA were also related [11] .…”
Section: Discussionmentioning
confidence: 52%
“…CKD patients had multiple risk factors for LVH including traditional risk factors e.g., age, comorbid diseases, ischemic heart disease, and CKD related risk factors e.g.,volume overload, anemia, malnutrition, uremia [13] . Reported prevalences of LVH assessed by echocardigram in KT recipeints varied from 33 to 67% that might be related with a difference in modes of dialysis before KT and post-transplant duration [14] , [15] , [16] , [17] , [18] , in this study the prevalence of LVH was 39% during the mean 3.45 years of post-KT duration. Previous studies found that KT can improve these risk factors and result in a decrease of LVH prevelence from 67 to 75% in pre-transplant to 37–52.1% in 1 year post-transplant patients and the regression of LVH was related with a reduction of serum Cr and improvement of BP control and anemia [14] , [15] .…”
Section: Discussionmentioning
confidence: 54%
“…The development of heart failure is a clinically silent process and it is often diagnosed late during disease progression; therefore, early diagnose is a critical issue. If we identify the at‐risk population during early‐stage we may prevent or delay progression of cardiac dysfunction 31 . We also found a moderate and significant positive correlation between SDI values and elapsed time from the first hemodialysis in hemodialysis group (Figure 4).…”
Section: Discussionmentioning
confidence: 61%